2020
DOI: 10.3390/biom10091204
|View full text |Cite
|
Sign up to set email alerts
|

Cellular and Molecular Mechanism of Cardiac Regeneration: A Comparison of Newts, Zebrafish, and Mammals

Abstract: Cardiovascular disease is the leading cause of death worldwide. Current palliative treatments can slow the progression of heart failure, but ultimately, the only curative treatment for end-stage heart failure is heart transplantation, which is only available for a minority of patients due to lack of donors’ hearts. Explorative research has shown the replacement of the damaged and lost myocardium by inducing cardiac regeneration from preexisting myocardial cells. Lower vertebrates, such as the newt and zebrafis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 120 publications
(246 reference statements)
0
9
0
Order By: Relevance
“…During tissue regeneration, lost cell types need to be replaced through de novo differentiation of tissue resident stem cells or from pre-existing differentiated cells (Poss, 2010). Several vertebrate species, such as zebrafish or newts, can regenerate a wide variety of tissues, such as appendages (Sehring and Weidinger, 2020;Tanaka, 2016), heart muscle (de Wit et al, 2020;González-Rosa et al, 2017;Xiang and Kikuchi, 2016) or retina (Alunni and Bally-Cuif, 2016;Wan and Goldman, 2016). By contrast, mammals have lost most of their regenerative potential and repair injured tissues through imperfect wound healing, which can lead to scar formation and fibrosis (Eming et al, 2014;Erickson and Echeverri, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…During tissue regeneration, lost cell types need to be replaced through de novo differentiation of tissue resident stem cells or from pre-existing differentiated cells (Poss, 2010). Several vertebrate species, such as zebrafish or newts, can regenerate a wide variety of tissues, such as appendages (Sehring and Weidinger, 2020;Tanaka, 2016), heart muscle (de Wit et al, 2020;González-Rosa et al, 2017;Xiang and Kikuchi, 2016) or retina (Alunni and Bally-Cuif, 2016;Wan and Goldman, 2016). By contrast, mammals have lost most of their regenerative potential and repair injured tissues through imperfect wound healing, which can lead to scar formation and fibrosis (Eming et al, 2014;Erickson and Echeverri, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…12,13 Research on zebrafish and newts has shown that after injury preexisting cardiomyocytes can reenter the cell cycle and divide to repopulate the damaged region with new cardiac myocytes. [14][15][16] In mammals, myocyte proliferation is abundant during embryonic development and for up to 7 days after birth but declines thereafter to a very low rate. [17][18][19][20] It is clear that in adult mammals, cardiac myocyte regeneration is not a major contributor to post-MI cardiac repair.…”
mentioning
confidence: 99%
“…The adult mammalian heart has a very limited regenerative capacity, which causes permanent myocardial loss and insufficient repair after myocardial injury 1 . Identifying molecules that promote cardiomyocyte proliferation and cardiac regeneration is essential to provide novel strategies for myocardial protection 2 . The cardiac apical resection (AR) model of neonatal mice has revealed a strong regenerative capacity of the heart within 7 days after birth 3 , 4 .…”
Section: Introductionmentioning
confidence: 99%